2005
DOI: 10.1104/pp.104.057646
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dwarfing Mutation in a Green Revolution Gene from Brassica rapa  

Abstract: Mutations in the biosynthesis or signaling pathways of gibberellin (GA) can cause dwarfing phenotypes in plants, and the use of such mutations in plant breeding was a major factor in the success of the Green Revolution. DELLA proteins are GA signaling repressors whose functions are conserved in different plant species. Recent studies show that GA promotes stem growth by causing degradation of DELLA proteins via the ubiquitin-proteasome pathway. The most widely utilized dwarfing alleles in wheat (Triticum aesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 42 publications
2
47
0
1
Order By: Relevance
“…The LHR I-VHIID-LHRII region may function as a DNA-binding domain, analogous to the basic leucine zipper protein-DNA interaction (30), with the LHRs mediating protein-protein interactions and the VHIID motif mediating protein-DNA interactions. Recently, Muangprom et al (31) reported that conserved amino acid sequences near the VHIID motif play an important role in plant size determination; a novel Q-to-R mutation near the VHIID motif in the REPRESSOR OF ga1-3 (RGA) homologue of Brassica rapa results in a gibberellininsensitive dwarf. Moreover, the same mutation in Arabidopsis RGA also confers a dwarf phenotype in transgenic Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…The LHR I-VHIID-LHRII region may function as a DNA-binding domain, analogous to the basic leucine zipper protein-DNA interaction (30), with the LHRs mediating protein-protein interactions and the VHIID motif mediating protein-DNA interactions. Recently, Muangprom et al (31) reported that conserved amino acid sequences near the VHIID motif play an important role in plant size determination; a novel Q-to-R mutation near the VHIID motif in the REPRESSOR OF ga1-3 (RGA) homologue of Brassica rapa results in a gibberellininsensitive dwarf. Moreover, the same mutation in Arabidopsis RGA also confers a dwarf phenotype in transgenic Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the DELLA domain is only present in the DELLA proteins and is essential for their degradation in response to GA, although it is not required for F-box protein binding. A number of DELLA gain-of-function mutations have been described; all except one are located in the DELLA regulatory domain (Peng et al, 1997(Peng et al, , 1999Boss and Thomas, 2002;Chandler et al, 2002;Muangprom et al, 2005). Deletions or specific missense mutations of the conserved motifs (DELLA and/or VHYNP) within the DELLA domain render the mutant proteins resistant to GA-induced degradation, leading to a GA-insensitive dwarf phenotype Gubler et al, 2002;Itoh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise role of the DELLA domain in GA-mediated degradation is not known. In Brassica rapa, a novel GRAS domain mutation affects the ability of the encoded DELLA protein to interact with the F-box component of the SCF E3 Ub ligase, resulting in its accumulation and insensitivity to GA (Muangprom et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, dwarf genes have been utilized in plant breeding as represented by the success of the "Green Revolution" in rice and wheat (Hedden 2003;Khush 2001). Furthermore, GA 1 -and GA 3 -deficient dwarf mutant rosette (ros; Rood et al 1989) and the semidominant GA-insensitive dwarf mutant caused by a gain-of-function mutation in the C-terminal GAI, RGA, SCARECROW (GRAS) domain of a REPRESSOR OF GA1-3 (RGA) homolog, Brrga1-d (Muangprom et al 2005), have been reported in B. rapa, and are expected to reduce lodging problems of oilseed Brassica cultivars without affecting the harvest.…”
mentioning
confidence: 99%